Membrane equilibration for in situ dissolved gas instrumentation: a comparison of four approaches - Colson, Beckett C.; Michel, Anna P. M. (Frontiers in Membrane Science and Technology, 2025)
Many in situ dissolved gas instruments use a membrane inlet to extract gas from water enabling measurement in the gas phase. However, mass transport across membranes is slow, making it difficult to build instruments with fast time responses. Several approaches exist to improve time response, including pulling vacuum to enhance gas flux, but the trade-offs between different approaches are unclear. Starting from first principles, we present a set of analytical models describing the operation of four different approaches for operating a membrane-based dissolved gas instrument. Using these models, we obtain the steady state and dynamic performance characteristics of each approach, and identify design trade-offs between speed, sensitivity, and complexity. Insights from these models enable physics-based design decisions and design optimization instead of instrument designers needing to rely on empirical methods.